2021
DOI: 10.4049/jimmunol.2000087
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of S100a8 and S100a9 Enhances Skin Hyperplasia and Promotes the Th17 Response in Imiquimod-Induced Psoriasis

Abstract: High concentrations of the damage-associated molecular patterns S100A8 and S100A9 are found in skin and serum from patients suffering from psoriasis, an IL-17–related disease. Notably, although the expression of these proteins correlates with psoriatic disease severity, the exact function of S100A8 and S100A9 in psoriasis pathogenesis remains unclear. In this study, we investigated the role of S100A8 and S100A9 in psoriasis-associated skin hyperplasia and immune responses using S100a8−/− and S100a9−/− mice in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
(89 reference statements)
2
13
0
Order By: Relevance
“…Several recent studies revealed that S100A8 and S100A9 are also expressed in fibroblasts, keratinocytes, and other cell components of the skin. S100A8 and S100A9 were robustly upregulated in skin tissues under pathological conditions, such as psoriasis, atopic dermatitis, and wounds, and they contributed to development of these pathological processes [10][11][12]. In wounded skins, S100A8 and S100A9 expression were induced to promote fibroblast activation and dermal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies revealed that S100A8 and S100A9 are also expressed in fibroblasts, keratinocytes, and other cell components of the skin. S100A8 and S100A9 were robustly upregulated in skin tissues under pathological conditions, such as psoriasis, atopic dermatitis, and wounds, and they contributed to development of these pathological processes [10][11][12]. In wounded skins, S100A8 and S100A9 expression were induced to promote fibroblast activation and dermal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the mice imiquimod-induced psoriasis model, the abrogated activity of extracellular S100A8 and S100A9 increased PASI and elevated the production of IL-17. Additionally, S100A8 regulated differentiation and inhibited proliferation of keratinocytes; thus, prevented the development of skin hyperplasia (53). An almost unchanged level of S100A8 in our study might have had an ameliorating effect on the severity of psoriasis and might slightly reduce the level of IL-17.…”
Section: Discussionmentioning
confidence: 51%
“…IF analysis confirmed significant upregulation of Amphiregulin (AREG) and SERPINB2 in Exp vs. Nby comparison at the protein level ( Figure 5D ). Notably, S100A8 , the downregulated gene, was the damage-associated molecular in skin disorders and will be secreted under inflammatory microenvironment ( Defrêne et al, 2021 ). Its downregulation suggested the degree of inflammatory response was attenuated over time.…”
Section: Resultsmentioning
confidence: 99%